QCD axion dark matter in the dark dimension - Hai-Jun Li (Journal of High Energy Physics)
Abstract The recently proposed dark dimension scenario reveals that axions can be localized on the Standard Model brane, thereby predicting the quantum chromodynamics (QCD) axion decay constant from the Weak Gravity Conjecture: f a ≲ M 5 ~ 109 – 1010 GeV, where M 5 is the five-dimensional Planck mass. When combined with observational lower bounds, this implies that f a falls within a narrow range f a ~ 109 – 1010 GeV, corresponding to the axion mass m a ~ 10 −3 – 10 −2 eV. At this scale, the QCD axion constitutes a minor fraction of the total cold dark matter (DM) density ~ 10 −3 – 10 −2. In this work, we investigate the issue of QCD axion DM within the context of the dark dimension and demonstrate that the QCD axion in this scenario can account for the entire DM abundance through a simple two-axion mixing mechanism. Specifically, we consider the resonant conversion of an axion-like particle (ALP) into the QCD axion. We find that, in a scenario where the ALP possesses a mass of approximately m A ~ 10 −5 eV and a decay constant of f A ~ 1011 GeV, the QCD axion in the dark dimension can account for the overall DM. The ALP required within this specific range may originate from the grand unification of gauge forces in the dark dimension.